1993
DOI: 10.1111/j.1600-051x.1993.tb00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingivitis, plaque accumulation and plaque composition under long‐term use of Meridol®

Abstract: The effectiveness of amine fluoride and stannous fluoride in the prophylaxis of caries and gingivitis is well-known from the literature. The aim of this study was to assess whether these agents could be recommended for long-term use. Under conditions of a clinical double-blind study, the influence of an amine/stannous fluoride rinse on gingivitis, plaque accumulation and the composition of the supragingival plaque was tested over a period of 7 months. 102 persons with signs of chronic gingivitis participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 11 publications
(4 reference statements)
5
53
1
Order By: Relevance
“…The decrease in the total probe count in the AmF/SnF 2 toothpaste + AmF/SnF 2 rinse group correlates with clinical findings showing a decrease in plaque index after the use of these products [Zimmermann et al, 1993;Mengel et al, 1996]. The total probe count of the plaque samples after the AmF/SnF 2 toothpaste + water rinse period was between those after the toothpaste + AmF/SnF 2 rinse and after the toothpaste + no rinse periods.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The decrease in the total probe count in the AmF/SnF 2 toothpaste + AmF/SnF 2 rinse group correlates with clinical findings showing a decrease in plaque index after the use of these products [Zimmermann et al, 1993;Mengel et al, 1996]. The total probe count of the plaque samples after the AmF/SnF 2 toothpaste + water rinse period was between those after the toothpaste + AmF/SnF 2 rinse and after the toothpaste + no rinse periods.…”
Section: Discussionsupporting
confidence: 49%
“…The difference in composition between the first fluoride-free period and the other fluoride-free periods may, in addition to the Hawthorne effect, be related to the fact that the first period was preceded by a 2-week period in which NaF toothpaste had been used, while the others were preceded by a period when AmF/SnF 2 toothpaste had been used. Clinical studies have shown that AmF/SnF 2 exerts a different pressure on plaque composition than NaF [Zimmermann et al, 1993;Mengel et al, 1996]. The differences between the other periods, which were randomized, should be fully related to the various experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…If plaque re-growth is less or delayed, or less binding sites are available in the dental plaque, less fl uoride will be taken up. Inhibition of plaque accumulation has been observed after using AmF/SnF 2 dentifrice and/or mouthrinse in several studies [Zimmermann et al, 1993;Mengel et al, 1996;Paraskevas et al, 2004]. If AmF/SnF 2 had a similar effect on plaque growth in the present study, then this could have reduced fl uoride uptake.…”
Section: Discussionmentioning
confidence: 75%
“…In a 7-year clinical study using a combination of amine fluoride products a 43% reduction in DMFS mean values was found (Künzel et al, 1977). The effects of Sn 2 F or AmF/Sn 2 F containing products on plaque accumulation were examined by many investigators (Øgaard et al, 1980;Bánóczy et al, 1989;Zimmermann et al, 1993;Mengel et al, 1996;Madléna et al, 2004;Gerardu et al, 2007). Madléna et al (2009) proved the beneficial effects of amine fluoride /stannous fluoride containing products on periodontal parameters in patients treated with fixed orthodontic appliances.…”
Section: Halitosis Tooth and Tongue Gel Amine Fluoride Gel (See Below)mentioning
confidence: 99%